ENGINEERING AIR CONDITIONING SYSTEMS ON THE JABODEBEK LIGHT RAIL TRANSIT TO ANTICIPATE AIRBORNE DISEASE TRANSMISSION - Mahandhika , Asrofi
At the end of 2019, a series of pneumonia-like cases emerged in China. WHO named the disease caused by SARS-CoV-2 as COVID-19. SARS-CoV-2 transmission can occur through droplets, airborne, fomit and other media. Public transportation such as LRT is at high risk for SARS-CoV-2 transmission, especially due to airborne. ASHRAE recommends preventing through engineering of air conditioning systems. Therefore it is necessary to do research in the form of redesign of the air conditioning system on the LRT which can further minimize the spread of SARS-CoV-2. In this study, redesign will be carried out on the air conditioning system on the LRT in order to better anticipate COVID-19. The first step that was done was to analyze the current condition of the LRT air conditioning system related to the potential spread of SARS-CoV-2. The next step is calculate and determine the type of system design that is most suitable and feasible. In the final section an analysis of the selected systems is carried out based on the consideration of the spread of SARS-CoV-2 and thermal comfort. This study shows that the current system allows cross-contamination of SARS-CoV-2 spread due to airflow pattern and filter efficiency of only 12–20%. The design recirculation system is considered as the most suitable and feasible system. The system modifies air flow pattern for return air and increases the air filter rating. In the proposed system, SARS-CoV-2 cross-contamination due to airflow can be minimized and the better indoor air quality due to higher filter efficiency.